Revised Annual Plan 1989-90 Seventh Five Year Plan 1985-90 Union Territory of Pondicherry - Planning Commission (Planning Commission, 1989)
During the year 1988-89, due to late and inadequate release of canal water to Karaikal Region, the rice bowl of this Union Territory of Pondicherry, the double cropped paddy area has been converted into single cropped paddy area in 2496 Hect. in Pondicherry Region also, the delayed monsoon and drawdown of water table in the tube wells has resulted in reduction in Kharif area coverage. However the shortfall occurred in Kharif season has been compensated by bringing an additional area of 2966 hect. against the area of 5900 hect* targeted for Rabi 1988-89 season. Even though all extension efforts were taken by this Administration, only an area of 11282 hect. could be brought under Paddy as against the normal area of 135CC Hect.
Union Territory of Pondicherry